2022
DOI: 10.3390/nu14235036
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Single Dose of Citrulline on the Physical Performance of Soccer-Specific Exercise in Adult Elite Soccer Players (A Pilot Randomized Double-Blind Trial)

Abstract: Purpose: The purpose of this study was to evaluate the effect of a single intake of citrulline at 3 g and 6 g doses in adult elite soccer players performing sport-specific exercise. Materials and Methods: This randomized double-blind placebo-controlled study analyzed 18 soccer players from the top divisions of three European countries. Participants were randomized into three groups of six each and performed a field-based soccer-specific test for 18 min. Comparative analysis of heart rate, fatigue and post-exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…In the present study, like most studies in this field, assessment of these proposed mechanisms is limited and indirect at best. Blood lactate concentrations and heart rate, as surrogates of energy metabolism and cardiovascular responses, respectively, were not affected by CM supplementation, which is consistent with previous findings for lactate concentration (Bezuglov et al., 2022; Chappell et al., 2020; Farney et al., 2019; Rhim et al., 2020; Trexler, Keith, et al., 2019; Wax et al., 2015; Wax et al., 2016) and heart rate (Farney et al., 2019; Glenn et al., 2017; Wax et al., 2015; Wax et al., 2016). These measures are considered as indicators of the intensity of exercise and whole‐body physiological stress, but do not provide any mechanistic insight into ergogenicity of CM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, like most studies in this field, assessment of these proposed mechanisms is limited and indirect at best. Blood lactate concentrations and heart rate, as surrogates of energy metabolism and cardiovascular responses, respectively, were not affected by CM supplementation, which is consistent with previous findings for lactate concentration (Bezuglov et al., 2022; Chappell et al., 2020; Farney et al., 2019; Rhim et al., 2020; Trexler, Keith, et al., 2019; Wax et al., 2015; Wax et al., 2016) and heart rate (Farney et al., 2019; Glenn et al., 2017; Wax et al., 2015; Wax et al., 2016). These measures are considered as indicators of the intensity of exercise and whole‐body physiological stress, but do not provide any mechanistic insight into ergogenicity of CM.…”
Section: Discussionsupporting
confidence: 92%
“…The ergogenic effects of CM supplementation have been equivocal to date. A series of studies have reported no effects of CM on short‐duration exercise performance (Bezuglov et al., 2022; Chappell et al., 2020, 2018; Cunniffe et al., 2016; Farney et al., 2019; Gonzalez et al., 2018; Trexler, Keith, et al., 2019; Wax et al., 2015), while others have documented ergogenic effects (Glenn et al., 2017; Pérez‐Guisado & Jakeman, 2010; Wax et al., 2016). For example, CM (8 g dextrose + 8 g CM) supplemented 1 h before a resistance exercise protocol in 15 trained females resulted in an improvement in upper‐ and lower‐body performance measured by number of repetitions performed (Glenn et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggests no improvement in anaerobic performance following CM ingestion. This is in agreement with Bezugulov et al who had 18 elite adult soccer players consume a single dose of either 3g or 6g CM 1-hour prior to performing a field-based soccer test 24 . No differences were found in physical performance between groups or when compared to PLA.…”
Section: Discussionsupporting
confidence: 91%